Formulation and Market Acceptability of Dragon Fruit (Selenicerius undatus) Flavored Mead - Josiefel Z. Agcaoili (PLANTA TROPIKA, 2025)
This paper discusses the development and acceptability of Mead wine flavored with Dragon Fruit. A quantitative descriptive analysis survey was utilized among forty (40) panelists who are experts in alcohol. At the same time, 75 respondents were randomly selected as participants in the sensory analysis using a Hedonic rating scale with a 5-point Likert scale. The results of the study have shown that the product was acceptable, considering its color, aroma, taste, and even the alcohol content of both treatments. In the findings, the highest response on color is ruby with 62.5%, and responses on aroma are regarded as sweet, tangy, and even zesty nuance. The taste reveals that it is fairly acceptable, with a 2.30 mean, which accounts for its acidity and is good for food pairing. On the overall acceptability level of the three coded samples, the wine-coded control got the highest description of high acceptable and a mean of 4.38. As for the willingness to purchase the product, the commercial product got the highest mean of 4.13, acceptable, and wine with code treatment 1 got a high score of 4.03, which is also acceptable. The results of this study imply that mead with added dragon fruit has the potential to produce mead that is preferred by respondents.